The Combined Effects of Toxic Microcystis aeruginosa and Thermal Stress on the Edible Clam (Corbicula fluminea): Insights into Oxidative Stress Responses and Molecular Networks - Jingxiao Zhang; Ning Wang; Zehao Zhang; Yunni Gao; Jing Dong; Xiaofei Gao; Huatao Yuan; Xuejun Li (MDPI AG, 2023)
Cyanobacterial blooms (CYBs) have become a global environmental issue, posing risks to edible bivalves. Toxic cyanobacteria and thermal stress represent the two key co-occurring stressors to bivalves experiencing CYBs. To investigate the combined effects of these stressors on the edible bivalve Corbicula fluminea, the responses to oxidative stress and the molecular mechanisms of physiological adaptations in C. fluminea were examined under co-exposure to toxic Microcystis aeruginosa and thermal stress. The activity of antioxidant enzymes, including GST, SOD, CAT, GPx and GR, was significantly influenced by the interaction between temperature and M. aeruginosa (p < 0.05). A positive correlation was observed between toxic M. aeruginosa exposure and elevated SOD and GPx activities at 30 °C, demonstrating that SOD and GPx may help C. fluminea defend effectively against MCs under thermal stress. Furthermore, significant interactive effects between toxic M. aeruginosa and temperature were also observed in ROS and MDA (p < 0.05). The results of the PCA and IBR index also evidenced the apparent influence of toxic M. aeruginosa and thermal stress on oxidative stress responses of C. fluminea. The eggNOG and GO annotations confirmed that a substantial portion of differentially expressed genes (DEGs) exhibited associations with responses to oxidative stress and transporter activity. Additionally, KEGG analysis revealed that abundant DEGs were involved in pathways related to inflammatory responses, immune functions and metabolic functions. These findings improve our understanding of the mechanism of the physiological adaptation in bivalves in response to cyanotoxins under thermal conditions, potentially enabling the evaluation of the viability of using bivalves as a bioremediation tool to manage CYBs in eutrophic waters.